Nominal Contracts in a Bimetallic Standard - Garber, Peter M. (American Economic Review, 1986)
As its central feature, a bimetallic standard grants nominal debtors an option to deliver either of two metals. With results from the option pricing literature, construction of a formula to evaluate the bimetallic option in debt instruments is straightforward. With this formula, one can compute the option value in a wide range of nineteenth-century U.S. Treasury securities. Posession of the option values permits an adjustment of the yields on U.S. securities to make them comparable to yields on nonmetallic European securities. Evaluating the option allows the estimation of transfers from debtors to creditors. Copyright 1986 by American Economic Association.